A Original Research Hubungan Indeks Massa Tubuh (IMT) dan Low Density Lipoprotein Cholesterol (LDL-C) dengan Tekanan Darah pada Pasien Poli Jantung di RSUD Provinsi NTB - Lendi Leskia Putri; Yusra Pintaningrum; Fitriannisa Faradina Zubaidi (Lombok Medical Journal, 2023)
Hypertension is one of the leading causes of death worldwide. According to data from the World Health Organization (WHO) in 2019, hypertension affects more than 22% of the global population. The results from Riskesdas indicate an increasing prevalence of hypertension in Indonesia, from 25.8% to 34.1%. Body Mass Index (BMI) has a significant impact on the occurrence of hypertension, where individuals with excess BMI and obesity have a higher risk of developing hypertension. The increase in hypertension cases is also caused by dyslipidemia. LDL-C ratio is a strong predictor of atherosclerosis plaque formation, which can lead to increased blood vessel resistance and elevated blood pressure. This study aims to analyze the relationship between Body Mass Index (BMI) and Low Density Lipoprotein Cholesterol (LDL-C) with Blood Pressure. The design of this study was correlational research design with a cross sectional approach. The population in this study were all patients of polyclinic cardiology RSUD Provinsi NTB (November 2022-January 2023), with the sampling technique used was consecutive sampling, where size of sample is 28 peoples. Obtained data are analyzed using Spearman method. Overall there were 28 subjects. There were 4 (14.3%) subjects with underwight range, 7 (25%) with healthy weight range, 16 (57.2%) with overweight range, and obesity range. While for LDL-C levels, there were 8 (28.5%) with optimal, Fairly good, Borderline high, High, and very high. 5 (18%) out of 28 respondents have optimal BP, 7 (25%) with normal BP whereas in high BP were 57%. Stastistical analysis shows that there was no relationship between the value of BMI with blood pressure with p-value 0,765 (p>0,05; r = 0,059). there was no relationship between LDL-C with blood pressure (r = 0,044; p = 0,823).